The Frandidate - Benton, Jim (Franny K. Stein, mad scientist, 2009)
Determined to be elected class president, mad scientist Frannie K. Stein uses her Atomic Combiner to create a suit that makes her seem to be whatever a voter wants her to be, but the suit has plans of its own.